Clinical Recommendations for the Use of Recombinant Human Erythropoietin in Patients with Hepatitis C Virus Being Treated with Ribavirin - Morris Sherman; Lawrence Cohen; Mary Anne Cooper; Magdy Elkashab; Victor Feinman; David Fletcher; Nigel Girgrah; Jenny Heathcote; Mark Levstik; William B McNaull; David Wong; Florence Wong; et al. (Canadian Journal of Gastroenterology)
Today, combination antiviral therapy with pegylated interferon-alpha and ribavirin (RBV) allows many patients infected with hepatitis C virus (HCV) to achieve a sustained virological response, which is equivalent to cure. Data also support the clinical benefit of combination antiviral therapy in patients coinfected with HCV and HIV, and in patients who have received a liver transplant.